Antibiofilm properties of selected Lactobacillus species and their mechanism of action against Listeria monocytogenes - Thantsha, Mapitsi Silvester (University of Pretoria, 2022)
Dissertation (MSc (Microbiology))--University of Pretoria, 2022.